Effects of Plasma Pretreatment on ZnO Deposition by SILAR on SiO2, HfO2, and Glass Substrates. Issue 8 (19th July 2018) - Higgins, Marissa; Pintor‐Monroy, Maria Isabel; Quevedo‐Lopez, Manuel
Abstract: Zinc oxide (ZnO) films are deposited onto glass, silicon oxide, and hafnium oxide substrates via the successive ionic layer adsorption and reaction (SILAR) method. The substrates are subjected to an oxygen plasma treatment prior to the deposition to increase the hydrophilic character of the film surface and improve the morphological and structural properties of the resulting ZnO films. Crystallinity, surface morphology, and thickness of the films with and without the plasma treatment are thoroughly evaluated by multiple characterization techniques. The oxygen plasma treatment increases the substrate's surface roughness significantly which results in an increase in the nucleation sites. The plasma treatment yields thicker films in all the substrates compared with substrates without the plasma treatment. The thickness of the ZnO deposited on glass substrates increases as the rinsing time increases, while the opposite is observed for films deposited on both silicon and hafnium oxide substrates. The higher porosity of the ZnO films grown on silicon dioxide and hafnium dioxide substrates leads to a higher surface area that increases the removal of the deposited ZnO on these substrates with the rinsing during the SILAR deposition, resulting in an overall thickness reduction of the film. Abstract : Zinc oxide (ZnO) is deposited by successive ionic layer adsorption and reaction on different substrates where the effects on the ZnO growth are evaluated by the use of an oxygen plasma pretreatment. The plasma allows the growth mechanism and quality of films to be evaluated. The plasma pretreatment also increases the surface roughness, creating a more hydrophilic surface, and promotes the growth of larger grain sizes. .